Language as a social phenomenon: inter-subjectivity and the pragmatic dimension (Actual Problems of Mind, 2017)
The paper attempts in answering the question of why the language can be considered a social phenomenon. The author alines herself with the B.A. SerebryakofF’s conception of language as (1) universal social phenomenon of a necessary character, and (2) unique phenomenon unlike to any other.
Keywords: language; Sociality; Social phenomenon; Egocentric words; Pragmatics; Intersubjectivity